Understanding quit decisions in primary care: a qualitative study of older GPs. Issue 2 (19th February 2016) - Sansom, Anna; Calitri, Raff; Carter, Mary; Campbell, John
Abstract : Objective: To investigate the reasons behind intentions to quit direct patient care among experienced general practitioners (GPs) aged 50–60 years. Design and setting: Qualitative study based on semistructured interviews with GPs in the South West region of England. Transcribed interviews were analysed thematically. Participants: 23 GPs aged 50–60 years: 3 who had retired from direct patient care before age 60, and 20 who intended to quit direct patient care within the next 5 years. Results: The analysis identified four key themes: early retirement is a viable option for many GPs; GPs have employment options other than undertaking direct patient care; GPs report feeling they are doing an (almost) undoable job; and GPs may have other aspirations that pull them away from practice. Findings from this study confirmed those from earlier research, with high workload, ageing and health, family and domestic life, and organisational change all influencing GPs' decisions about when to retire/quit direct patient care. However, in addition, GPs expressed feelings of insecurity and uncertainty regarding the future of general practice, low morale, and issues regarding accountability (appraisal and revalidation) and governance. Suggestions about how to help retain GPs within the active clinical workforce were offered, covering individual, practice and organisational levels. Conclusions: This research highlights aspects of the current professional climate for GPs that are having an impact on retirement decisions. Any future changes to policy or practice to help retain experienced GPs will benefit from this informed understanding of GPs' views. Key factors to take into account include: making the GP workload more manageable; managing change sympathetically; paying attention to GPs' own health; improving confidence in the future of general practice; and improving GP morale.